The Kibble-Zurek mechanism at exceptional points - Balázs Dóra (Nature Portfolio, 2019)
Universal non-equilibrium behaviour can emerge in physical systems when they are driven through a parameter regime where their energy gap closes. Dóra et al. show that the Kibble-Zurek scaling associated with exceptional points in non-Hermitian systems is distinct from the conventional Hermitian result.